Dysmenorrhea and Practice of Menstrual Hygiene in Adolescent Females - Lilik Ariyanti; Warih Anjari Dyah Kusumaningayu; Fatchurrohmah Ines Prabandari; Alinda Nur Ramadhani (Gaster, 2024)
Background: Adolescence is a relatively fast period of physical change experienced by adolescents when puberty is marked by the first menstruation (menarche). Menstruation and menstrual habits continue to encounter numerous social, cultural, and religious barriers, which make it extremely difficult to maintain good hygiene during the menstrual cycle. Objective: Analyzing menstruation practices and the prevalence of dysmenorrhea in adolescent female is the goal of this study.   Method: The cross-sectional investigation was carried out in Sukoharjo and Surakarta. The research was carried out between December 2023 and January 2024. Adolescent female samples had reached menarche. WaLIDD score is an instrument used to measure dysmenorrhea. Results: The results of this study show as many as 71.7% of Menarche adolescent girls at the age of 12-14 years. As many as 44.4% of respondents said dysmenorrhea almost always interfered with work activities. Data also shows that nearly 100 % of respondents wash their hands before and after replacing menstrual materials. The majority of them wash their genitals using soap (79.1%) and replace pads (>3 times) 72.5%. Conclusion: Most respondents practice good menstrual hygiene, characterized by frequent washing of hands and genitals. Adolescent females who are knowledgeable about their periods can make hygienic and safe menstrual habits.